IS THE AICHR AN UNWANTED HUMAN RIGHTS BODY IN THE ASEAN? THE ANSWER FROM THE INTERNATIONAL ORGANIZATIONAL LAW PERSPECTIVE - Rachminawati (Padjadjaran Journal of International Law, 2022)
The AICHR is a remarkable achievements of ASEAN after having the ASEAN Charter in 2007. However, since the TOR of AICHR has a serious institutional defect that makes the AICHR unable to protect peoples’ human rights, the AICHR could not be act as a human rights guardian in the region. It leads to the question whether the ASEAN and its member states want the body to be established to protect the people in the region? The answer to this question is important to figure out the future human rights mechanisms in the region. The question will be addressed through qualitative and normative legal research. Field research was conducted to resolve some questions that are not provided in the literature to enrich the understanding on the topic from the ASEAN elites, practioner, and academicians. It finds that The institutional defect and less political support showed that ASEAN and its member states do not want to have a reliable regional human rights mechanism. However, it finds that there was an evolutionary approach that has been conducted by the AICHR despite that situation to promote human rights in the region. The study suggests the AICHR to use strong words of the TOR and the ASEAN Charter to enhance their performance and reliability. A new approach for human rights mechanisms that sets in a formal way; under a legal-binding instrument are more favorable. Therefore, if the AICHR show that characteristic, it will be supported by the ASEAN and its member states.